Transcystic versus transcholedochal laparoscopic common bile duct exploration: Choosing the right approach – A Case Series - Singgih Annas Fuadhi; Adeodatus Yuda Handaya; Agus Barmawi; Imam Sofii; Nurcahya Setyawan (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2023)
Laparoscopic common bile duct exploration (LCBDE) is a relevant therapeutic option in managing cholecysto-choledocholithiasis. The success of this procedure is highly dependent on selecting an appropriate method, either transcystic or transcoledocal. Intraoperative choledochoscopy proves its importance in evaluating the condition of the choledochal duct and sphincter of Oddi. In this case series, we report 2 cases of patients with complaints of right upper abdominal pain and jaundice. Both patients were diagnosed with multiple cholecysto-choledocholithiasis at Dr. Sardjito Hospital, Yogyakarta. The interventional measures applied to both patients were transcystic and transcoledocal exploration. In the first patient, the transcystic method was chosen because the cystic duct was widening up to 9 mm in diameter. While in the second patient, the transcoledocal method was taken because the diameter of the cystic duct was still within normal limits. The duration of surgery in transcystic surgery was shorter than in transcoledocal surgery, with a time ratio of 129 minutes versus 162 minutes. Postoperatively, both patients were discharged on the second day after the procedure, and both experienced recovery without any significant complications. Overall, LCBDE has been shown to be safe to perform. The one-stage surgical approach has been shown to reduce the risk of complications, cost, and duration of treatment required. The choice between the transcystic or transcoledocal method should be based on each patient’s clinical condition.